Analysis of Expropriation and Investment Dispute Resolution in the Case of Venezuela Holdings v. Venezuela (ICSID Case No. ARB/07/27) - Suryani, Cendana (JURNAL MAHASISWA YUSTISI, 2025)
Foreign investment plays a crucial role in the global economy by driving economic growth and development in host countries. To protect foreign investors, many countries have signed Bilateral Investment Treaties (BITs) that regulate protection against both direct and indirect expropriation. Direct expropriation occurs when a state takes over or reduces the value of an investment directly, usually involving the transfer of ownership or rights over investor assets without adequate compensation. Under international law, expropriation must be conducted for a public purpose, be non-discriminatory, and be accompanied by fair compensation. The case of Venezuela Holdings v. Venezuela illustrates how the Venezuelan government, through nationalization in 2007, directly expropriated assets belonging to Mobil Corporation without offering compensation equal to fair market value. This case discusses the legality of expropriation, the amount of compensation owed, and the relevance of BIT provisions requiring host states to protect foreign investments. In this context, indirect expropriation — as seen in other cases — is also relevant, where government policies reduce investment value without direct asset seizure. As a result, BITs must balance host country interests with investor rights to ensure fair and transparent protection against nationalization or expropriation policies.